Bench to bedside review of myositis autoantibodies - Boaz Palterer; Gianfranco Vitiello; Alessia Carraresi; Maria Grazia Giudizi; Daniele Cammelli; Paola Parronchi (Clinical and Molecular Allergy, 2018)
Abstract Idiopathic inflammatory myopathies represent a heterogeneous group of autoimmune diseases with systemic involvement. Even though numerous specific autoantibodies have been recognized, they have not been included, with the only exception of anti-Jo-1, into the 2017 Classification Criteria, thus perpetuating a clinical-serologic gap. The lack of homogeneous grouping based on the antibody profile deeply impacts the diagnostic approach, therapeutic choices and prognostic stratification of these patients. This review is intended to highlight the comprehensive scenario regarding myositis-related autoantibodies, from the molecular characterization and biological significance to target antigens, from the detection tools, with a special focus on immunofluorescence patterns on HEp-2 cells, to their relative prevalence and ethnic diversity, from the clinical presentation to prognosis. If, on the one hand, a notable body of literature is present, on the other data are fragmented, retrospectively based and collected from small case series, so that they do not sufficiently support the decision-making process (i.e. therapeutic approach) into the clinics.